Regulatory disciplines on the mobility of service professionals: Lessons from Regional Trade Agreements - Antonia Giulia Carzaniga; Swati Sharma (World Trade Organization (WTO), 2022)
When it comes to services traded through the international movement of individuals (mode 4), Regional Trade Agreements (RTAs) have increasingly adopted trade-facilitating disciplines that both build upon and innovate the GATS framework. By analysing relevant provisions of RTAs, we are able to identify trends and commonalities in approach. We find that mode 4 RTA disciplines address mostly aspects related to transparency and application procedures. With the exception of low-income economies, these provisions have been adopted in RTAs concluded by WTO Members across all income levels and all geographic regions, albeit with differing intensity. This points to the potential for some of the improvements and innovations captured in RTAs to be considered in a wider, possibly multilateral, context.
Keywords: F13; F15; F22; L8; K33; 330; temporary movement of natural persons; GATS mode 4; Regional Trade Agreements; regulatory disciplines